Low-temperature creation of Frenkel defects via hot electron-hole recombination in highly pure NaCl single crystals - Lushchik, A.; Lushchik, Ch.; Nagirnyi, V.; Shablonin, E.; Vasil’chenko, E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
The creation spectrum of stable F centres (being part of F–H pairs of Frenkel defects) by synchrotron radiation of 7−40 eV has been measured for highly pure NaCl single crystals at 12 K using a highly sensitive luminescent method. It is shown that the efficiency of F centre creation in a closely packed NaCl is low at the decay of anion or cation excitons (7.8−8.4 and 33.4 eV, respectively) or at the recombination of relaxed conduction electrons and valence holes. Only the recombination of nonrelaxed (hot) electrons with holes provides the energy exceeding threshold value EFD, which is sufficient for the creation of Frenkel defects at low temperature.